Perception and Level of Awareness of Climate Change among Adult Learners on Attendance and Performance in Literacy Centres, Ondo State, Nigeria - Francis O. Olaniyi (RIRAI Publisher, 2020)
This study investigated theperception and awareness of climate change among adult learners on attendance and performance in literacy centres in Ondo State, Nigeria. Five research questions were generated for the study. The descriptive research design of the survey type was used for the study involving a population of adult learners in literacy centres in Ondo State, Nigeria. Purposive random sampling technique was used to select a sample size of 100 participants drawn from the entire population of adult learners in literacy centres of Ondo State, Nigeria. A self-constructed questionnaire was used as an instrument for the study. Data collected were analysed using descriptive statistics of frequency counts,percentage and mean deviation were used to answer the research questions raised for the study. Findings revealed that the level of awareness on climate change among adult learners on attendance and performance is very high because they were already aware of climate change and its effects on human existence. Also, adult learners do not perceive climate change as the work of nature alone but as well as the effects of activities of man on the environment. Findings also revealed that that several factors like deforestation, bush burning, air pollution and other man’s activities on the environment such as mining, science and technology among others are the causes of climate change. It is therefore recommended that, information should be disseminated to the people on proper management of the environment. Government should not relent in conducting house to house orientation on how to conserve the environment from the effects of climate change.